THE STUDENT’S ABILITY TO WRITE A GOOD PARAGRAPH THROUGH DISCUSSION AT THE SECOND YEAR STUDENTS OF SMAN 1 PAKEL TULUNGAGUNG - Suparmo Suparmo (Journal of English for Academic and Specific Purposes (JEASP), 2019)
As members of society, we are necessarily trained in writing activities, at least in creating sentences to good paragraphs. However, there are reasons how to read is not enough, and we are also interested in how to write sentences very well (Zamel, 1987: 257). Writing a good paragraph is a complex process that has been done and not easy for everyone. From four language skills, writing a composition is considered as a subject that is difficult to master.  Mastery of writing is not a skill which can be learned in isolation. It means that writing is integrated by the other language skills such as reading, speaking, and listening, (Richard Rodger (1999:56). The usage of acceptable technique is essential in teaching-learning process because it motivates the students to learn English. Therefore, the writer provides a research question on whether the students have created their composition easily through a peer-to-peer discussion. In this case, the writer needs to observe whether there are different results of composing a paragraph through a peer-to-peer discussion compared with the other groups. The objectives of the study are whether students using the discussion to write a good paragraph gain better scores in English than those who do not. The writer collects the data from the students of the second year. They were asked to write a paragraph based on specific topics provided by a classroom teacher and choose three alternative topics to write quickly. The first process was that the students were trained to write a paragraph in a group. Next, in the final activity, they create a composition. The result of research about making composition through a discussion way is right. They can share each other to correct the mistakes. With the result of the discussion, the students can create the composition better the next day. The research concludes that making composition through a discussion way is one of the solutions to make composition easier for the students. Based on the result of research, the students enjoy writing a paragraph through discussion way.